2019
DOI: 10.3390/su11195247
|View full text |Cite
|
Sign up to set email alerts
|

Future Skills of Design for Sustainability: An Awareness-Based Co-Creation Approach

Abstract: Our inner, invisible dimension consisting of our values, mental models and worldviews, has been identified as a significant leverage point for transformational change, as it brings to life our actions. Accordingly, the inner dimension of sustainability has a major role in transitioning towards desirable and sustainable futures. This paper focuses on exploring what kind of methods and competences are needed to access and work with the inner dimension as part of collaborative design practices aiming for sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…The implementation of the latter requires specialists who possess sufficient knowledge and skills in a certain sphere, especially in the niche of sustainable entrepreneurship, which serves as the basis for the sustainable development of financial relations in society [23]. Due to the depth of such transformations, it is necessary to change not only documents and rules, but it is also necessary to change values in the social model, worldview patterns [24]. In this regard, there is a need to study the patterns of development and the peculiarities of the tax situation in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the latter requires specialists who possess sufficient knowledge and skills in a certain sphere, especially in the niche of sustainable entrepreneurship, which serves as the basis for the sustainable development of financial relations in society [23]. Due to the depth of such transformations, it is necessary to change not only documents and rules, but it is also necessary to change values in the social model, worldview patterns [24]. In this regard, there is a need to study the patterns of development and the peculiarities of the tax situation in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al [34] showed that environmentbased research in the last 10 years has focused on consumer perception and behaviour towards hotels' environmental practices [27], in addition to showcasing the conceptual or technical model of effective environmental management systems [37], evaluation methods or factors to determine the most effective environmental management systems [38][39][40][41] and marketing and management initiatives for hotels' environmental practices [38]. Green human resource management practice is increasingly recognized as a key factor to support environmental management training within hospitality organizations [42]. However, few studies have investigated specific skills needs and skills gaps and the barriers to implementation of environmental practices, relevant to their advancement in Welsh tourism [16].…”
Section: Sustainability Skills In Tourism and Hospitality 221 Greementioning
confidence: 99%
“…These findings relate to the entrepreneur couple's personal experiences, to workshop practices with local stakeholders, and to the seasonal employee recruitment process and its outcomes. Since more detailed descriptions of the last two have already been presented elsewhere (see Hakio and Mattelmäki 2019), they are discussed here only briefly. The workshops took place at the beginning of the project in 2017 (figure 1, also Annex A and university workshops), when 30 local stakeholders gathered together with the entrepreneurs to co-sense and conceive new openings for service concepts and collaboration.…”
Section: The First Lens: Everyday Encountersmentioning
confidence: 99%
“…In a nutshell, the entrepreneurs wanted to give the new employees space to interpret, embrace, and implement the guiding values of the place as they wished. This co-creative approach allowed the employees to self-direct and realize their own internal visions, and thus manifest a caring work and service culture in various forms (see Hakio & Mattelmäki 2019). The impacts of the practices and atmosphere created by the employees were experienced by the customers, which in turn generated a lot of positive customer feedback during the season.…”
Section: The First Lens: Everyday Encountersmentioning
confidence: 99%